2020
DOI: 10.2478/helm-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed homologous genes reveal interspecies differences of Paragonimus proliferus based on transcriptome analysis

Abstract: SummaryParagonimus proliferus (P. proliferus), one of 46 Paragonimus species registered in the National Center for Biotechnology Information database, may be much more widely distributed in Southeast Asia than previously thought, as its reported natural foci have increased in the past decades. However, very little is known about its molecular biology, especially at the transcriptome level. For the first time, the transcriptome of this species was sequenced and compared with four other common Paragonimus specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Since the publication of an earlier review on gene diversity and genetic variation in Paragonimus (Blair et al ., 2016 ), genomes and/or transcriptomes of several Paragonimus species have been published (Li et al ., 2016 ; Oey et al ., 2019 ; Li et al ., 2020 ; Rosa et al ., 2020 ). In some respects, the datasets generated by these studies revealed findings that were expected: genes of Paragonimus species have many homologues in other foodborne trematodes (Oey et al ., 2019 ).…”
Section: Discussion and Questions For Future Investigationmentioning
confidence: 99%
“…Since the publication of an earlier review on gene diversity and genetic variation in Paragonimus (Blair et al ., 2016 ), genomes and/or transcriptomes of several Paragonimus species have been published (Li et al ., 2016 ; Oey et al ., 2019 ; Li et al ., 2020 ; Rosa et al ., 2020 ). In some respects, the datasets generated by these studies revealed findings that were expected: genes of Paragonimus species have many homologues in other foodborne trematodes (Oey et al ., 2019 ).…”
Section: Discussion and Questions For Future Investigationmentioning
confidence: 99%
“…The global epidemiology of paragonimiasis has been well described and will not be repeated here in full (Madariaga et al ., 2007; Procop, 2009; Chai, 2013; Diaz, 2013; Fischer and Weil, 2015; Blair, 2019). Over 50 species have been described though many are not known to cause human disease (Blair, 2019; Li et al ., 2020). Briefly, P. westermani complex is endemic to large parts of East and Southeast Asia, as are P. heterotremus and P. skrjabini which are also present in parts of India (Lane et al ., 2009; Chai, 2013).…”
Section: Epidemiologymentioning
confidence: 99%
“…Paragonimus kellicotti is a trematode and one of over 50 known species of Paragonimus (Blair, 2019; Li et al ., 2020). Paragonimus species typically infect hosts through ingestion of infected crustaceans, although the potential for infection also exists through ingestion of raw mammalian meat (Blair, 2019).…”
Section: Introductionmentioning
confidence: 99%